WOMAN'S ATTITUDE ABOUT MENOPAUSE COMPLAINTS AT THE PUBLIC HEALTH CENTER KEBUN HANDIL JAMBI CITY - Arifarahmi Arifarahmi (Jurnal Akademika Baiturrahim Jambi, 2019)
A woman get into perimenopause at the age of 40 and will experience menopause at the age of 51.5 years. The type of menopause consists of natural menopause, perimenopause, and menopause, postmenopause. Negative impacts that occur during menopause can occur physical changes and changes in psychology. Physical changes that often occur in postmenopausal women are most commonly experienced, namely hot flush (81.3%), insomnia (65.3%), the vagina becomes dry (58.7%), joint pain (57.3%) whereas psychological changes are easily offended (81%), anxiety (64%), memory decreases (44%), stress (33.3%). This research used description method with a cross-sectional  design  of woman’s attitude about menopause complaints at the public health center Kebun Handil. This study was conducted on September 4th – 7th 2018. Samples were 40 people by using accidental sampling technique. The collecting of data used a questionnaire. Data was used analyzed as univariate. The Result showed about women have a less good attitude about menopause complaints were 22 women (55%). It is concluded that woman’s attitude toward menopause complaints are still less good. As input for health promotion efforts in the community, especially for women to provide information and education regarding complaints of menopause.